Enzymatic degradability of diclofenac ozonation products: A mechanistic analysis - Dorothee Schmiemann; Florian Bicks; Indra Bartels; Arno Cordes; Martin Jäger; Jochen Stefan Gutmann; Kerstin Hoffmann-Jacobsen (Chemosphere, 2024)

Heart Rate Variability from Underwater Spiroergometry: How Meaningful? - Andreas Koch; Fabian Möller; Elena Jacobi; Thomas Muth; Clark Pepper; Uwe Hoffmann; Jochen D. Schipke (Journal of Science in Sport and Exercise, 2023)

Enzymatic post-treatment of ozonation: laccase-mediated removal of the by-products of acetaminophen ozonation - Dorothee Schmiemann; Lisa Hohenschon; Indra Bartels; Andrea Hermsen; Felix Bachmann; Arno Cordes; Martin Jäger; Jochen Stefan Gutmann; Kerstin Hoffmann-Jacobsen (Environmental Science and Pollution Research, 2023)
Ozonation is a powerful technique to remove micropollutants from wastewater. As chemical oxidation of wastewater comes with the formation of varying, possibly persistent and toxic by-products, post-treatment of the ozonated effluent is routinely suggested. This study explored an enzymatic treatment of ozonation products using the laccase from Trametes versicolor . A high-performance liquid chromatography coupled with high-resolution mass spectrometry (HPLC-HRMS) analysis revealed that the major by-products were effectively degraded by the enzymatic post-treatment. The enzymatic removal of the by-products reduced the ecotoxicity of the ozonation effluent, as monitored by the inhibition of Aliivibrio fischeri. The ecotoxicity was more effectively reduced by enzymatic post-oxidation at pH 7 than at the activity maximum of the laccase at pH 5. A mechanistic HPLC-HRMS and UV/Vis spectroscopic analysis revealed that acidic conditions favored rapid conversion of the phenolic by-products to dead-end products in the absence of nucleophiles. In contrast, the polymerization to harmless insoluble polymers was favored at neutral conditions. Hence, coupling ozonation with laccase-catalyzed post-oxidation at neutral conditions, which are present in wastewater effluents, is suggested as a new resource-efficient method to remove persistent micropollutants while excluding the emission of potentially harmful by-products. Graphical abstract

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Oyster Reef Surfaces in the Central Wadden Sea: Intra-Reef Classification and Comprehensive Statistical Description - Jan Hitzegrad; Leon Brohmann; Kai Pfennings; Tom K. Hoffmann; Anne K. Eilrich; Maike Paul; Mario Welzel; Torsten Schlurmann; Jochen Aberle; Achim Wehrmann; Nils Goseberg (Frontiers in Marine Science, 2022)
The Pacific oyster ( Magallana gigas ) is an invasive species in the Wadden Sea transforming parts of it permanently. M. gigas , as an ecosystem engineer, builds reef structures that are characterized by highly complex and variable surfaces consisting of densely packed, sharp-edged individuals connected with cement-like bonds. To investigate the interactions between reef structure, shape and formation and wave as well as tidal currents, an understanding of the surface roughness is essential. This work reports on observations of oyster reefs for which seven new structural classes ( Central Reef , Transitional Zone , Cluster I , Cluster II , Patch I , Patch II , and Garland ) are proposed. For each class, high resolution Digital Elevation Models (DEMs) have been elaborated based on Structure-from-Motion (SfM) photogrammetry and analyzed using spatial statistics. By determining probability density functions (PDFs), vertical porosity distributions, abundances, orientations and second-order structure functions (SSFs), topographical parameters that influence the hydraulic bed roughness have been determined. The results suggest, that by applying the structural classification and their distinct topographical roughness parameters, the oyster reef surfaces can be described appropriately accounting for their complexity. The roughness accounts to a total roughness height k t = 103 ± 15 mm and root-mean-square roughness height k rms = 23 ± 5 mm. These values were found similar across all structural classes, yet the shape of the PDFs reveal differences. With decreasing abundance, the distributions become more positively skewed and are characterized by more extreme outliers. This is reflected in the higher statistical moments, as the skewness ranges between Sk = 0.4–2.1 and the kurtosis between Ku = 2.2–11.5. The analysis of the orientations and the SSFs confirms anisotropic behavior across all structural classes. Further, the SSFs reveal the oyster shells as significant roughness elements with exception of Cluster I and II , where the clusters are identified as significant roughness elements. The provided set of topographical roughness parameters enhances the knowledge of oyster reef surfaces and gives insights into the interactions between biogenic structure and surrounding hydrodynamics. The new intra-reef classification allows for more accurate determination of the overall roughness as well as the population dynamics of the habitat forming oyster. Combined with hydraulic measurements, the results can be used to estimate the hydraulic bed roughness induced by the oyster reef surfaces.

Quantitation of norovirus-specific IgG before and after infection in immunocompromised patients - Suliman Qadir Afridi; Hassan Moeini; Behnam Kalali; Jochen Martin Wettengel; Oliver Quitt; Raphaela Semper; Markus Gerhard; Ulrike Protzer; Dieter Hoffmann (Brazilian Journal of Microbiology, 2020)

Expert-based ex-ante assessments of potential social, ecological, and economic impacts of upgrading strategies for improving food security in rural Tanzania using the ScalA-FS approach - Frieder Graef; Götz Uckert; Jana Schindler; Hannes Jochen König; Hadijah A. Mbwana; Anja Fasse; Lutengano Mwinuka; Henry Mahoo; Laurent N. Kaburire; Paul Saidia; Yusto Mugisha Yustas; Valerian Silayo; et al. (Food Security, 2017)

Mechanisms of hepatotoxicity associated with the monocyclic β-lactam antibiotic BAL30072 - Franziska Paech; Simon Messner; Jochen Spickermann; Mathias Wind; Anne-Hortense Schmitt-Hoffmann; Anne Therese Witschi; Brett A. Howell; Rachel J. Church; Jeff Woodhead; Marc Engelhardt; Stephan Krähenbühl; Martina Maurer (Archives of Toxicology, 2017)

Optische Genregulation in Mikrobioreaktoren - Peter M. Kusen; Kyra Hoffmann; Georg Wandrey; Jochen Büchs; Jörg Pietruszka (BIOspektrum, 2017)

Neuroprotection of medical IOP-lowering therapy - Norbert Pfeiffer; Julia Lamparter; Adrian Gericke; Franz H. Grus; Esther M. Hoffmann; Jochen Wahl (Cell and Tissue Research, 2013)

Discovery and genetic characterization of novel caliciviruses in German and Dutch poultry - Sandro Wolf; Jochen Reetz; Kathrin Hoffmann; Anne Gründel; Bernd-Andreas Schwarz; Ingrid Hänel; Peter H. Otto (Archives of Virology, 2012)

The importance of drawdown and sediment removal for the restoration of the eutrophied shallow Lake Kraenepoel (Belgium) - Jeroen Van Wichelen; Steven Declerck; Koenraad Muylaert; Ivan Hoste; Vanessa Geenens; Jochen Vandekerkhove; Erik Michels; Niels De Pauw; Maurice Hoffmann; Luc De Meester; Wim Vyverman (Hydrobiologia, 2007)

Volatiles modulate the development of plant pathogenic rust fungi - Kurt Mendgen; Stefan G. R. Wirsel; Andreas Jux; Jochen Hoffmann; Wilhelm Boland (Planta, 2006)